A Framework for Screening and Risk Assessment for Priority Assessment Chemicals in China - Yu, Xiangyi; Mao, Yan; Lin, Jun (Journal of Environmental Accounting and Management, 2026)
The abuse of toxic and hazardous chemicals has caused environmental pollution and harmed human health. As a result, chemical risk management has become a hot research topic around the world, and sound chemicalmanagement has become a key objective of sustainable development. Based on the concept of chemical risk management, many developed countries have identified toxic and harmful chemicals among their existing chemicals, and have prioritized assessment of the most dangerous chemicals and of chemicals that create a high risk of environmental exposure. Their goal has been to support a comprehensive risk assessment that will guide the implementation of risk management. This management model has been widely recognized by the international community, particularly in developed nations, but has not been fully implemented in developing nations. By analyzing three mature international risk assessment methods, we identified potential solutions for establishing methods that are most suitable for the current situation in China. Based on our literature review, we propose a screening method, the “criteria comparison method”, and a two-stage risk assessment method to prioritize the assessment of chemicals in China. The screening method proposed in this paper focuses on the hazards created during their manufacture and use based on the internationally accepted Globally Harmonized System hazard classification theory and principles, to ensure that the method is scientific and easy to operate. The proposed two-stage risk assessment method is mainly based on risk theory (risk = hazard × exposure), which fully considers the technical capability of chemical risk assessment in China. The screening and risk assessment methods will help decision-makers to screen potentially hazardous chemicals and carry out risk assessment for China’s priority assessment chemicals, thereby providing support for improving management of chemical risks in China.